Advertisement from the Minister of Heath Regarding Multimodal Analysis in COVID-19 - Mutia Nursyafitri Nasution; Alemina Br. Perangin angin; Umar Mono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study talks about how to use multimodal analysis in a covid-19 advertisement. This study is trying to figure out what the covid-19 ad looks like and how it makes you think. It also wants to look at the linguistic and visual aspects of the messages. This is how the research was done: It used a qualitative method, which meant that the data were taken from YouTube and then turned into five images. This study uses Halliday's theory to figure out how Cheong talks and uses visual elements (GSP). In the covid-19 ad, there are visible and linguistic elements that show the process of GSP. As you can see, there are five leads, one display, five primary announcements, five secondary announcements, one call and visit, and one tag for each. Material Process 11, Actors 6, Circumstances 3, Location 1, and Goals 10 are all parts of the linguistic ideation function.